Business mathematics - Dickman, Greg. (South Melbourne : Nelson, 1997)
This book is about: Use of calculators and basic mathematical operations; Business applications of percentages; Linear graphs and break-even analysis; Depreciation; Simple interest; Compound interest; ...
Keywords: Business mathematics; Business mathematics